Pengaruh Influencer Marketing Dan Brand Trust Terhadap Keputusan Pembelian Produk Skincare Glad2glow Dengan Minat Beli Sebagai Variabel Mediasi Di Kota Malang - Nurul Ain Aqila; Siti Asiyah; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstrak This study examines the effect of influencer marketing and brand trust on purchasing decisions for Glad2Glow skincare products, with purchase intention as a mediating variable. A quantitative explanatory approach was employed involving 75 consumers of Glad2Glow skincare products in Malang City selected through purposive sampling. Data were collected using structured questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4.0. The findings reveal that influencer marketing does not significantly affect purchasing decisions, while brand trust has a positive and significant effect on purchasing decisions. Influencer marketing has a positive but insignificant effect on purchase intention, whereas brand trust significantly and positively influences purchase intention. Furthermore, purchase intention significantly and positively affects purchasing decisions. Mediation analysis indicates that purchase intention does not mediate the relationship between influencer marketing and purchasing decisions but successfully mediates the effect of brand trust on purchasing decisions. These results suggest that strengthening brand trust plays a more crucial role than influencer marketing in encouraging consumers to develop purchase intention and ultimately make purchasing decisions for Glad2Glow skincare products. Keyword: Influencer marketing, Brand trust, Purchase Intention, Purchase Decision